2019
DOI: 10.1080/10888438.2019.1659277
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Deficits in Reading Fluency and/or Spelling

Abstract: Deficits in reading fluency and in spelling can dissociate during development, resulting in groups with reading deficit only (RD), spelling deficit only (SD) and combined reading and spelling deficit (RSD). The current study investigated the one-to-two-year longitudinal stability of these subgroups in 167 German-speaking children. Reading fluency deficits (irrespective of spelling skills) were stable over time, while spelling deficits were stable in the RSD-group but not in the SD-group. Lower stability in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
(57 reference statements)
1
11
0
2
Order By: Relevance
“…Reading ability is highly stable. Moll et al (2020) examined the one‐ to two‐year stability of deficits in reading and spelling in 167 German‐speaking children aged 9 years at the first point of assessment. The correlation between performance at the first time point and one year later was very high for reading fluency ( r > .9) and high for spelling ( r = .78).…”
Section: Outcomes For Children With Reading Disordersmentioning
confidence: 99%
“…Reading ability is highly stable. Moll et al (2020) examined the one‐ to two‐year stability of deficits in reading and spelling in 167 German‐speaking children aged 9 years at the first point of assessment. The correlation between performance at the first time point and one year later was very high for reading fluency ( r > .9) and high for spelling ( r = .78).…”
Section: Outcomes For Children With Reading Disordersmentioning
confidence: 99%
“…Research on transparent orthographies such as Dutch has shown that both word reading and spelling are related (Schaars et al, 2017). In another study on another relatively transparent orthography, namely German, it was found that improvement in spelling among primary school children was associated with good performance in reading (Moll et al, 2019).…”
Section: Multicomponential Approach For Assessing Reading and Readingmentioning
confidence: 97%
“…In English, RAN digits uniquely predicted decoding skills in first graders but not RAN colors ( Compton, 2003 ). In transparent orthographies, RAN letters and digits have also been found to significantly differentiate readers with and without reading disabilities ( de Jong and van der Leij, 2003 ; Furnes and Samuelsson, 2010 ; Torppa et al, 2012 ; Moll et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is perhaps the reason why it is so di cult, in research, to study reading uency and, in education, to help learners improve it (Torgesen and Hudson 2006;Wexler et al 2008; but see Breznitz et al 2013;Horowitz-Kraus et al 2014a). Reading uency de cits are stable over time (e.g., Leinonen et al 2001;Moll et al 2019) and conspicuous in different types of orthographies: in consistent or shallow ones where the print-to-speech mapping is regular (e.g., Landerl and Wimmer 2008), and in inconsistent or deep ones where the mapping is complex and not entirely rulebased (Katzir et al 2004). Dys uent reading is the most persistent impairment in dyslexia (Shaywitz et al 2008), and its lead symptom in readers of consistent orthographies (Landerl et al 2013;Seymour et al 2003;Torppa et al 2010;Ziegler et al 2010).…”
Section: Introductionmentioning
confidence: 99%